Faktor Anggaran Biaya Proyek Konstruksi Terhadap Pembangunan Negara - Yeprian Aji Ratukarangga; Imam aldino (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
The research aims to detail the factors influencing the budget of construction projects and analyze their impact on national development. This study is expected to contribute valuable insights for government decision-makers, project planners, and relevant stakeholders. Consequently, collaborative efforts can be undertaken to enhance budget management efficiency, ensure the smooth progress of construction projects, and support sustainable growth and overall national development. The research employs a literature review methodology, involving activities related to data collection from existing literature, reading and note-taking, as well as organizing research materials. The findings highlight that, in nation-building, the size and complexity of construction projects play a crucial role in determining their impact on national development. Large-scale infrastructure projects have the potential to improve connectivity, provide better access to communities, and support economic growth. However, challenges such as risk management, regulations, and fluctuations in building material prices require a holistic approach in planning, implementation, and management